Concrete : design, construction, examples - Peck, Martin, ....- (Basel : Birkhäuser, 2006)
With its virtually infinite plasticity, its constructional versatility, and its simple and straightforward building technology, concrete is the building material of the present. In addition to careful design and constructional planning, the invitation of bids and the building contract are the keys to a successful implementation. Building with Concrete provides the basic information needed to work with the material, with special attention to the architect's role in planning and construction management. It describes current trends in concrete technology and the development of innovative new types of concrete, with firsthand reports by architects in the field. It also describes the new version of the DBV/BDZ data sheet "Exposed Concrete."
Keywords: Architectuur; Beton; Bouwkunst; Concrete construction; Concrete -- Handbooks, manuals, etc; Concrete